Design and development of a dilute-phase flow pneumatic dryer for agricultural by-products - Rodulfo, Victor A. Jr (Philippine agricultural mechanization journal)
A pneumatic or flash dryer for agricultural products / by-products was designed, fabricated and tested for drying sapal (coconut meat residues) and ipil-ipil leaves. It is a semi-open drying system where part of the exhaust air is recirculated by a fan mounted on top of the drying chamber. The flow of the centrifugal type-fan is controlled by the rpm of its shaft. Air is heated as it passes through a 6 spiral type electric resistance heaters with a maximum heating capacity of 6.81 KW. Each heater has a switch to manually control drying air temperature. The particulates are fed at constant rate into the lower part of the dryer by a screw auger. The particulates are carried upward by the flowing hot air stream. The hot air stream causes the particulates to be suspended and ultimately be carried along and dried at the same time. The drying section is alternately made of stainless steel cylinders of varying sizes. The total length of the dryer is 275 cm. A cyclone is provided at the discharge end of the dryer to serve as collector of the dried product. The fabricated pneumatic drying system demonstrated that it can be used to dry agricultural by-products such as sapal and to dehydrate plant parts such as ipil-ipil leaves at high temperatures at a short-time duration. The study initially tested the functionality of the machine. Thus, further tests must be done to investigate the effects of drying at high temperatures on quality of product. Further, the economics of the machine and its multi-product applications must be evaluated.